If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(5*x)/9 = (3*x)/4-7 // - (3*x)/4-7
(5*x)/9-((3*x)/4)+7 = 0
(5*x)/9+(-3/4)*x+7 = 0
7-7/36*x = 0 // - 7
-7/36*x = -7 // : -7/36
x = -7/(-7/36)
x = 36
x = 36
| 3x-4=-50 | | 3/2x-7=x-5 | | 2(2x+2)=22 | | 4(-2x+3)=116 | | x+2(x+3)=3(x+2) | | X-64y^3=0 | | -3x+4=-36 | | 0=-5U-37 | | 2(x-4)-15=27 | | 3+w=-2 | | 1.2(x+5)=.5x-1 | | 2(x+4)=-3(2x-1) | | 8/24-1/9 | | 0.42/4.41 | | 4x+10=10x+7 | | 3x^3-35x^2+122x-120=0 | | 11y-10g-22=13 | | 18+z=37 | | 14-7x=.245 | | Log(x)=6.2 | | (x+6)(x-6)=B | | 97/(1-.3) | | 14+7x=.245 | | 120/(1-.3) | | 8x-(5x-7)=25 | | 171.34=120/(1-m) | | 100=75/(1-m) | | -3m+11=-6+5+4m | | 2(3(4)-1)-3(4(4)+3)-6=5x-4(4x-1) | | 120/1-51.34 | | 171.34-120/1-m | | 12m+23=179 |